Development of methods for citizen scientist mapping of residential woodsmoke in small communities. (1st June 2022) - Wagstaff, Matthew; Henderson, Sarah B.; McLean, Kathleen E.; Brauer, Michael
Abstract: Background: Residential wood burning is a major source of fine particulate matter (PM2.5 ) during winter and a leading contributor to air pollution. Exposure to woodsmoke PM2.5 is associated with many health effects, so it is important to characterize the magnitude and spatial variability in exposures. However, high infrastructure and maintenance costs of regulatory monitoring stations limit their spatial resolution and make monitoring infeasible for many small communities where woodsmoke may be prevalent. Methods: Mobile monitoring was conducted with a nephelometer and multi-wavelength aethalometer, capable of identifying woodsmoke PM2.5, to capture spatially resolved data. This Combined Aethalometer and Nephelometer for Assessment of Woodsmoke (CANAW) method was evaluated in three pairs of communities in British Columbia, Canada. Measurements were also taken at fixed-site monitoring stations. Light scattering measured by a nephelometer (Bsp ) was compared with gravimetric filter-based and beta-attenuation measures of PM2.5 . The difference in absorbance of 370 nm and 880 nm wavelengths as measured by an aethalometer ( delta C), was compared with the chemical woodsmoke tracer levoglucosan. Results: Fixed site measurements of Bsp and delta C were comparable with established methods of monitoring PM2.5 and woodsmoke, respectively. Correlations in each tested relationship across all locations were high (r ≥ 0.93 in all cases). Mobile monitoring captured high spatial variation in woodsmoke PM2.5 and maps of average concentrations during monitoring were created to identify woodsmoke hotspots. Conclusion: Following the successful implementation of the mobile CANAW method, training materials were created and tested with lay volunteers along with an online mapping application. Volunteers were able to effectively operate the equipment, collect valuable data on woodsmoke concentrations, and map spatial patterns across their communities using the application. The CANAW method is a valuable option for advancing cost-effective data collection for residential woodsmoke in otherwise unmonitored communities, and to add spatial context to existing monitoring networks. Highlights: Novel method to map particulate matter and woodsmoke pollution across communities (83). Effective monitoring technique for rural areas lacking air quality monitoring (79). Creation of tools for citizen scientists supports cost effective data collection (82). Abstract : The CANAW method was developed and evaluated to advance cost-effective data collection for woodsmoke PM2.5 in affected communities with high spatial resolution.